Microbial determinants of soil quality in mixed larch and birch forests: network structure and keystone taxa abundances - Ge, Zhaoxuan; Zhang, Xinyu; Liu, Chang; Li, Minghao; Wang, Ruihan; Zhang, Yang; Zhang, Zhidong (Frontiers in Plant Science, 2025)
Changes in forest soil microbial community characteristics affect soil function and quality. However, the mechanisms through which microbes drive soil quality across different stand types remain unclear. Three typical forest types, larch (Larix principis-rupprechtii) forest (LF), birch (Betula platyphylla) forest (BF), and mixed larch and birch forest (MF), were selected to assess soil properties, microbial community characteristics, and the complexity and stability of co-occurrence networks. The results showed that stand type significantly affected soil quality, microbial community composition, and network structure. Compared to LF stands, both MF and BF stands exhibited higher levels of soil organic carbon (SOC), total nitrogen (TN), available nitrogen (AN), available phosphorus (AP), maximum water holding capacity (MWHC), and soil quality index (SQI), with the SQI increasing by 54.29% and 48.57%, respectively. The bacterial Shannon index was lower in MF and BF stands, whereas the fungal Shannon index was higher. Fungal community composition was more sensitive to variations among the three stand types than bacterial communities. The MF stands exhibited higher microbial complexity and stability, with a higher relative abundance of keystone bacterial and fungal taxa associated with nutrient cycling and transformation. These findings suggest that SQI can be enhanced by increasing soil fungal diversity, improving microbial network complexity and stability, and increasing the relative abundance of key microbial taxa. This study emphasized that the mixing of larch and birch significantly affected soil microbial community characteristics, which in turn impacted soil nutrient utilization. The insights gained provide a deeper understanding of soil nutrient cycling in plantation ecosystems, offering valuable references for sustainable forest management practices.